Control of microbiologically influenced corrosion using ultraviolet radiation - Akrima Abu Bakar; Muhammad Khairool Fahmy Mohd Ali; Norhazilan Md. Noor; Nordin Yahaya; Mardhiah Ismail; Ahmad Safuan A. Rashid (Penerbit Universiti Kebangsaan Malaysia, 2017)
Baram Delta Operation had been producing oil and gas since 1960’s and serious pipelines failure was reported in the year of 2005. The final investigation has concluded that one of the species of bacteria that has been identified to cause microbiologically influenced corrosion, specifically known as sulfate reducing bacteria (SRB) was found to be one of the potential contributing factors to the incidents. This work investigates the potential use of ultraviolet (UV) radiation to inhibit the SRB consortium that was cultivated from the crude oil in one of the main trunk lines at Baram Delta Operation, Sarawak, Malaysia. The impact of UV exposure to bio-corrosion conditions on carbon steel coupon in certain samples for 28 days was discussed in this study. The samples were exposed to UV radiation based on variations of parameters, namely: time of UV exposure; and power of UV lamp. The significant changes on the amount of turbidity reading and metal loss of the steel coupon were recorded before and after experiment. The results showed that SRB growth has reduced rapidly for almost 90% after the UV exposure for both parameters as compared to the abiotic samples. Metal loss values were also decreased in certain exposure condition. Additionally, field emission scanning electron microscopy (FESEM) coupled with energy dispersive spectroscopy (EDS) was performed to observe the biofilm layer formed on the metal surface after its exposure to SRB. The evidence suggested that the efficiency of UV treatment against SRB growth could be influenced by the particular factors studied.